Preventing Uterine Cervix Cancer: The Clinical Meaning of Atypical Glandular Cells - Almeida, Gutemberg; Sainz, Jorge Eduardo; Fonseca, Renata; Chaves, Neil; Silva, Katia Silveira; Nunes, Julio; Furtado, Yara (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To determine the prevalence of the atypical glandular cells (AGCs) cytology and to analyze its clinical significance in different age ranges.Methods Retrospective observational study using computerized data from the Brazilian National Cancer Institute, including women screened between January 2002 and December 2008. The women included were those with an AGC result who were properly followed-up with colposcopy and a second cytology.Results A total of 132,147 cytopathological exams were performed during the study period. Five-hundred and thirty-three (0.4%) women with AGC cytology were identified and, of these, 69.41% (370/533) were properly referred for colposcopy and a new cytology. Most of the women (79.2%) with a 1st or 2nd AGC cytology were between the ages of 25 and 54 years. The 2nd cytology demonstrated 67.6% (250/370) of normality, 24.5% (91/370) of squamous atypia, and 6.2% (23/370) of AGC, 0.8% (3/370) adenocarcinoma in situ and 0.8% (3/370) adenocarcinoma invasor. On biopsy of the women with a second AGC cytology, 43.4% (10/23) had normal histology, 43.4% (10/23) had squamous lesions, 8.7% (2/23) had invasive adenocarcinoma, and 1.2% (1/23) had an inconclusive report. All of the women with high-grade squamous intraepithelial lesion (HSIL) or invasive adenocarcinoma (respectively 5 and 2 patients), after a 2nd AGC cytology were 25 years old or older.Conclusion The prevalence of the AGC cytology was low in the studied population. Most of the AGC cytology cases occurred in adult women between the ages of 25 and 54. Although most of the patients had normal histology after follow-up, several of them presented with squamous intraepithelial lesions or invasive adenocarcinoma.
Keywords: AGC; atypical glandular cells; glandular cervical neoplasia; Bethesda system; cervical cancer screening; cytology